Long-term experimental climate data for the energy and thermal comfort evaluation in built environment - Helena López-Moreno; María Nuria Sánchez-Egido; Ana Amelia Navarro-Fernández; Luis F. Zarzalejo-Tirado; Emanuela Giancola; María José Jímenez-Taboada; Silvia Soutullo-Castro (Anales de Edificación)
To define tailored climate change mitigation and adaptation strategies, the proposed methodology offers significant advantages. This approach is based on the generation of an updated experimental Typical Meteorological Year (TMYe) for the city of Madrid, utilizing meteorological variables recorded since 2008. In addition to comparing this TMYe with the widely used International Weather for Energy Calculations (IWEC) climate file, different future scenarios for 2050 and 2080 were projected following shared socioeconomic pathways. Finally, impact indicators at the climatic, urban, and building levels were evaluated. The results indicate that both the TMYe and its projections reveal increasingly warmer and drier climates, particularly in summer, with average summer temperatures of 32°C and 26% humidity by 2080 if no measures are taken. This implies a substantial increase in tropical nights, a higher thermal discomfort index, and a significant value of cooling degree-hours, not only in summer but also in spring and autumn.